Dynamic properties and avalanche noise analysis of 4H-SiC over wz-GaN based IMPATTs at mm-wave window frequency - Tripathy, P.R.; Mukherjee, M.; Pati, S.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
The mm-wave as well as noise properties of IMPATT diodes for the D-band are efficiently determined, with 4H-SiC and wurtzite type GaN as base materials, using advanced computer simulation techniques developed by the authors. The breakdown voltage (180 V) and efficiency (14.7%) is higher in case of 4H-SiC as compared to wz GaN based diode having the breakdown voltage (153 V) and efficiency (13.7%). The study indicates that 4H-SiC IMPATT diode is capable of generating high RF power density of about 8.383×10¹⁰ W/m² as compared to GaN IMPATT diode that is capable to develop the power density 6.847×10¹⁰ W/m² for the same frequency of operation. It is also observed that wz-GaN exhibits better noise behavior 7.42×10⁻¹⁵ V²·s than SiC (5.16×10⁻¹⁵ V² ·s) for IMPATT operation at 140 GHz. A tradeoff between the power output and noise from the device reveals that wz-GaN would be a suitable base material for high power application of IMPATT diode with moderate noise.